A scoping review to map research on children with dysgraphia, their carers, and educators. Issue 1 (2nd January 2022) - Kalenjuk, Elvira; Laletas, Stella; Subban, Pearl; Wilson, Sue
ABSTRACT: The aim of this scoping review was to systematically map and summarise recent peer-reviewed research on children with dysgraphia between 2015 and May 2021. The research included the perspectives of children, carers, and educators. Dysgraphia is a largely unrecognised specific learning disorder (SLD) in writing that manifests as a disability in handwriting, spelling, and/or composition skills during child development. Data from 77 studies from across five databases were charted to address four key questions and to direct future research. The findings included: (1) limited representations of participants using mostly quantitative methods; (2) children aged 9–14 as suitable for research recruitment; (3) thematic prevalence such as handwriting, spelling, and technology; and (4) low rates of international research output. Thus, future research may focus on compositional difficulties or research participants (children with dysgraphia, carers, and educators) sharing their lived experiences of dysgraphia. This may lead to improved awareness, professional development, and enhanced teacher resources.